2009
DOI: 10.1371/journal.pone.0006317
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of Lytic and Latent Gammaherpesvirus Infection in the Absence of the Inhibitory Receptor CEACAM1

Abstract: Control of gammaherpesvirus infections requires a complex, well orchestrated immune response regulated by positive and negative co-signaling molecules. While the impact of co-stimulatory molecules has been addressed in various studies, the role of co-inhibitory receptors has not been tested. The ITIM-bearing CEACAM1 is an inhibitory receptor expressed by a variety of immune cells, including B, T and NK cells. Using Ceacam1−/− mice, we analyzed the in vivo function of CEACAM1 during acute and latent murine gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Because KS is a highly angiogenic tumor, we wanted to investigate the induction of CEACAM1 expression by vIL-6. Furthermore, CEACAM1 and a CEACAM1 homolog have been shown to contribute to the pathogenesis of other herpesviruses, but the role of CEACAM1 during KSHV infection has not yet been investigated ( 47 , 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because KS is a highly angiogenic tumor, we wanted to investigate the induction of CEACAM1 expression by vIL-6. Furthermore, CEACAM1 and a CEACAM1 homolog have been shown to contribute to the pathogenesis of other herpesviruses, but the role of CEACAM1 during KSHV infection has not yet been investigated ( 47 , 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous microarray studies of immortalized dermal microvascular endothelial cells infected with KSHV also reported that the gene for CEACAM1 was one of multiple genes affected by KSHV infection ( 69 ). Furthermore, CEACAM1 was found to be upregulated in the lungs of mice infected with the murine gammaherpesvirus MHV68 ( 66 , 67 ). In the present study, we found that both KSHV latent and de novo infection of endothelial cells upregulated CEACAM1 expression compared to that in uninfected cells, and reactivation of PEL also resulted in increased CEACAM1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…We recently described that infection with MHV‐68 upregulates CEACAM1 on alveolar epithelial cells in lungs of WT mice (see Fig. 7 in ). CEACAM1 is an inhibitory receptor expressed by a variety of cells including NK cells .…”
mentioning
confidence: 89%
“…Interestingly, compared to WT mice, Ceacam1 −/− mice showed enhanced viral clearance in the lung (see Fig. in ). For human NK cells, it has been shown in vitro that homophilic CEACAM1 interactions can inhibit NK‐cell cytotoxicity against tumor cells .…”
mentioning
confidence: 90%
“…Among those are SIRPα and CEACAM1 and CEACAM3, members of the human carcinoembryonic antigen-related cell-cell adhesion molecule (CEACAM) family which have inhibitory ITIM/ ITSM motifs and activating ITAM-like motifs in their cytoplasmic regions, respectively [3,4]. A number of bacterial pathogens like pathogenic Neisseria (N. gonorrhoeae, N. meningitis) Haemophilus influenzae and Moraxella catarrhalis have been shown to bind to the N-terminal immunoglobulin (Ig) variable-like domain of CEACAM1 on epithelial and immune cells allowing both entry into the host by transcytosis and downregulation of the host's immune response by inhibiting adaptive and innate immune reactions [5][6][7][8][9][10][11]. Pathogens thus exploit the normal physiological function of CEA-CAM1 which acts as an immune inhibitory receptor on leukocytes upon homotypic or heterotypic interactions for example with other CEACAM members [7,12].…”
Section: Introductionmentioning
confidence: 99%